2018
DOI: 10.1530/eje-17-1017
|View full text |Cite
|
Sign up to set email alerts
|

The genetic characteristics of congenital hypothyroidism in China by comprehensive screening of 21 candidate genes

Abstract: ObjectiveCongenital hypothyroidism (CH), the most common neonatal metabolic disorder, is characterized by impaired neurodevelopment. Although several candidate genes have been associated with CH, comprehensive screening of causative genes has been limited.Design and methodsOne hundred ten patients with primary CH were recruited in this study. All exons and exon–intron boundaries of 21 candidate genes for CH were analyzed by next-generation sequencing. And the inheritance pattern of causative genes was analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
68
4
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 47 publications
10
68
4
1
Order By: Relevance
“…However, in the patient cohort, dH (n=32) was more common than Td (n=11). This result is in agreement with the data reported in china (27)(28)(29)(30)(31). Given that dH is largely caused by genetic Table Ⅱ.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…However, in the patient cohort, dH (n=32) was more common than Td (n=11). This result is in agreement with the data reported in china (27)(28)(29)(30)(31). Given that dH is largely caused by genetic Table Ⅱ.…”
Section: Discussionsupporting
confidence: 92%
“…However, phenotypic variability observed in patients with same mutations indicated the influence of other factors, such as genetic heterogeneity (15,34,42,43,(48)(49)(50). The present study found a high percentage (25.6%) of involvement of oligogenic mutations in studied cases, which is similar to that of previous studies simultaneously assessing multiple genes (15,(30)(31)(32). These studies reported frequent oligogenic involvement in cH, with oligogenic mutations in 20-43.5% of patients with cH and GiS and/or patients with Td in different ethnic populations.…”
Section: Minor Allele Frequencysupporting
confidence: 89%
See 3 more Smart Citations